2019
DOI: 10.1177/1479164119841536
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of choroidal changes following cataract surgery in patients with diabetes

Abstract: Objective: To study the structural changes in the choroid of diabetic patients following cataract surgery, using choroidal vascularity index and choroidal thickness. Methods: A prospective case–control study was conducted in 18 diabetic and 18 non-diabetic patients undergoing cataract surgery (phacoemulsification) in one eye. Enhanced depth imaging optical coherence tomography images were obtained before and after surgery. Niblack’s image binarization of images was performed to derive the choroidal vascularity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Ibrahim et al [54], using EDI-OCT, found that SFCT was significantly increased 1 week after PE and returned to the preoperative level at month 3 after surgery. However, conflicting results have been reported in studies on postoperative SFCT changes in diabetic patients, with some studies showing that SFCT increased after PE surgery in diabetic patients [55,56], while others have found no change [57,58], and yet others have shown a postoperative reduction in choroidal thickness [17]. In the present study, the SFCT increased at week 1 after surgery in the PE group and began to decline at month 3, but did not return to preoperative levels until month 12.…”
Section: Discussioncontrasting
confidence: 79%
“…Ibrahim et al [54], using EDI-OCT, found that SFCT was significantly increased 1 week after PE and returned to the preoperative level at month 3 after surgery. However, conflicting results have been reported in studies on postoperative SFCT changes in diabetic patients, with some studies showing that SFCT increased after PE surgery in diabetic patients [55,56], while others have found no change [57,58], and yet others have shown a postoperative reduction in choroidal thickness [17]. In the present study, the SFCT increased at week 1 after surgery in the PE group and began to decline at month 3, but did not return to preoperative levels until month 12.…”
Section: Discussioncontrasting
confidence: 79%
“…A number of publications have reported that phacoemulsification may cause a significant increase in choroid thickness [ 27 29 ]. However, some studies found no CT variation after cataract surgery in diabetics [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase of CVI after phacoemulsification was found, especially in the luminal vascular component [81,83]. The increased CVI may be associated with the choroidal inflammation induced by surgical trauma or with the intraocular pressure drop after cataract surgery [81,83].…”
Section: In Ocular Surgerymentioning
confidence: 95%